FlexTrail Printing as Direct Metallization with Low Silver Consumption for Silicon Heterojunction Solar Cells: Evaluation of Solar Cell and Module Performance. Issue 12 (8th December 2022) - Schube, Jörg; Jahn, Mike; Pingel, Sebastian; De Rose, Angela; Lorenz, Andreas; Keding, Roman; Clement, Florian
Abstract : The cover image shows an in‐situ photography of a nanosilver FlexTrail printing process being applied to high efficiency silicon heterojunction solar cells. Moreover, a scanning electron micrograph of a FlexTrail nanosilver electrode on an alkaline textured silicon heterojunction substrate is presented. Such electrodes exhibit a mean shading finger width of (12.7 ± 0.4) μm and allow for great silver saving. More details can be found in article number 2200702, Jörg Schube and co‐workers.